Assimilation of the Industrial Village concept by Japanese business circles at the turn of the 20th Century - Kikata, Junne; Nakae, Ken; Yokogawa, Haruka; Okada, Hanna (International Planning History Society Proceedings, 2016)
This study demonstrates the significance of a broader investigation into the assimilation of planning practices and concepts of western industrial villages by Japanese business circles. An early albeit lone example, is a 2016 introduction by Yorifusa Ishida describing Magosaburō Ohara’s achievement - a trial to develop an industrial village, and basic research on social reform - at the Kurashiki Bouseki Co Ltd. In addition, studies examining how Japanese academics, officials, and administrators, adopted the garden city idea primarily stem from their understanding of the writings of Ebenezer Howard (eg Watanabe, Katagi et al). However, few studies have examined Japanese business circles’ understanding of industrial villages as a broader basis for the Japanese adoption of garden city principles. In addition to schools of architecture, Japanese institutions of higher education such as schools of economics, agriculture, and law, collected books on western industrial villages. In general, schools of agriculture and economics had larger collections of books than schools of engineering, indicating that the idea of industrial villages, including the garden city, was accepted and taught in various contexts. Further, graduates in various fields of business could have recognized these ideas. Tokiyoshi Yokoi (1890-1927) introduced the idea of the garden city to Ohara. He taught at the Tokyo Imperial University School of Agriculture which collected books on the garden city movement. Hajime Seki (1873-1935), of the Tokyo College of Commerce, investigated the garden city concept when drafting the Kōjō Hō (the Manufacturing Act of 1911). His pupil, Masayoshi Tasaki (1880-1976), translated and introduced The Garden City Movement (1905) by G. M. Harris (with a preface by Howard) in 1917. Later, he proposed the development of a garden city for workers to the Mitsubishi Shipbuilding Co Ltd. By analysing an existing compendium of Japanese overseas travelers in the late 19th and the early 20th century, we can attain a thorough understanding of their experiences in the western industrialised environment. Business travel increased rapidly in the 1890s and by 1910 one-third of total overseas travel was attributable to business. These trips enabled Japanese businesses to assimilate concepts and practical information regarding western industrial villages. The Nikkō Electric Copper Smelting Co Ltd sent its core administrators to western countries. Manager Tsunesaburō Suzuki (1873-1940) traveled to Bournville in the United Kingdom in 1911 to meet George Cadbury and received advice about industrial management. Returning to Japan, he reformed his factory according to the principles of Onjō-Shugi (closely translated as Paternalism). In 1915, Manager Tetsutarō Hasegawa (1884- ?) wrote about Krupp’s welfare facilities and housing supply in Essen, Germany. The concept of western industrial villages was considered a means of business administration in Japanese business circles. Current evidence indicates that the primary transmission of the concept was related to planning; however, we argue that it emerged first in the rural industries of Japan.